Sustainable development of sewage sludge-to-energy in China: Barriers identification and technologies prioritization. (January 2017) - Ren, Jingzheng; Liang, Hanwei; Dong, Liang; Gao, Zhiqiu; He, Chang; Pan, Ming; Sun, Lu
Abstract: In order to promote the sustainable development of sludge-to-energy industry and help the decision-makers/stakeholders to select the most sustainable technology for achieving the sludge-to-energy target, this study aims at using grey Decision Making Trial and Evaluation Laboratory (DEMATEL) to identify the critical barriers that hinder the sustainable development of sludge-to-energy industry in China and to investigate the cause-effect relationships among these barriers. Accordingly, some policy implications for promoting the sustainable development of sludge-to-energy industry in China were proposed. After the grey DEMATEL analysis, a grey Multi-Criteria Decision Making (MCDM) framework which allows multiple decision-makers/stakeholders to use linguistic terms to participate in the decision-making for prioritizing the alternative technologies for sludge-to-energy was developed, and the evaluation criterion system for sustainability assessment of sludge-to-energy technologies was determined based on the results of grey DEMATEL analysis. Three alternative technologies for sludge-to-electricity were studied by the proposed MCDM method, and the results show that the proposed grey MCDM method is feasible for group decision-making and sustainability assessment of the alternative technologies for sludge-to-energy.